Recombinase-aided amplification coupled with lateral flow dipstick for efficient and accurate detection of Bombyx mori nucleopolyhedrovirus - Wang, Runpeng; Xu, Sheng; Wei, Erjun; He, Ping; Zhang, Yiling; Wang, Qiang; Tang, Xudong; Shen, Zhongyuan (Folia microbiologica, 2024)
The infection of Bombyx mori nucleopolyhedrovirus (BmNPV) is one of the main causes of economic losses in sericulture. Thus, it is essential to establish rapid and effective method for BmNPV detection. In the present study, we have developed a recombinase-aided amplification (RAA) to amplify the BmNPV genomic DNA at 37 °C within 30 min, and achieved a rapid detection method by coupling with a lateral flow dipstick (LFD). The RAA-LFD method had a satisfactory detection limit of 6 copies/μL of recombinant plasmid pMD19-T-IE1, and BmNPV infection of silkworm can be detected 12 h post-infection. This method was highly specific for BmNPV, and without cross-reactivity to other silkworm pathogens. In contrast to conventional polymerase chain reaction (PCR), the RAA-LFD assay showed higher sensitivity, cost-saving, and especially is apt to on-site detection of BmNPV infection in the sericulture production.
Keywords: bourec; Animals; Nucleopolyhedroviruses; Recombinase-aided amplification; techniky amplifikace nukleových kyselin; rekombinasy; DNA, Viral; Lateral flow dipstick; nukleopolyhedroviry; Sensitivity and Specificity; senzitivita a specificita; Recombinases; limita detekce; Bombyx; Nucleic Acid Amplification Techniques; Limit of Detection; zvířata; DNA virů; Bombyx mori nucleopolyhedrovirus